4D Printing Dual Stimuli-Responsive Bilayer Structure Toward Multiple Shape-Shifting - Ren, Luquan; Li, Bingqian; Liu, Qingping; Ren, Lei; Song, Zhengyi; Zhou, Xueli; Gao, Peng (Frontiers in Materials, 2021)
4D printing has been attracting widespread attention because its shape and performance can change under stimuli. The existing 4D printing technology is mostly limited to responsive to single stimulus, which means that the printing structure can only change under a pre-specified stimulus. Here we propose a 4D printing strategy with dual stimuli-responsive shape-shifting that responds to both temperature and water, by using a direct ink writing 3D printing method to deposit a polyurethane elastomer material with water-swelling characteristics on a heat-shrinkage shape memory polymer material to form a bilayer structure. Based on the systematic study of the adapted printing parameters of the polyurethane elastomer, the effect of programmable variables on the deformation shape was investigated. The diversified printing structure exhibits rich structural changes under one or both of the two stimuli of temperature and humidity. This research provides a universal multiple stimuli-responsive 4D printing method, which can effectively improve the intelligent responsiveness of 4D printing structures by combining multiple smart materials.